ROLE OF EDUCATION IN THE EMPOWERMENT OF WOMEN IN INDIA WITH SPECIAL REFERENCES TO KOTTAYAM DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
In the present article the title shows the word empower the women via education. This statement true to fulfill the empowerment of women in various fields. Also shows that empowerment of women in 21st century play important role in the development of the country. Education is the key factor for women empowerment, prosperity, development and welfare. Education is the key factor for women empowerment, prosperity, development and welfare. Discrimination of women from womb to tomb is well known. There is continued inequality and vulnerability of women in all sectors and women oppressed in all spheres of life, they need to be empowered in all walk of life. In order to fight against the socially constructed gender biases, women have to swim against the system that requires more strength. Such strength comes from the process of empowerment and empowerment will come from the education. And rural development will come from women empowerment. This paper aim to create the awareness among the women’s about different empowerment and identifying the impact of education in women overall empowerment in kottyam district.